Sistem Pakar Untuk Mendiagnosis Gangguan Jiwa Skizofrenia Menggunakan Metode Fuzzy Expert System (Studi Kasus Rs. Jiwa Menur Surabaya - Pradika, Alfian Angga; Jusak, Jusak; Lemantara, Julianto (Jurnal JSIKA, 2012)
Skizofrenia is a clinical syndrome with a variety of psikopatology, usually   severe , lasts long and the victim can be identified by a deviation from their thoughts, perceptions and emotions. There are many types of schizophrenia syndrome, Based on interviews with the doctor at Jiwa Menur mental hospital, schizophrenia syndromes ussually have similar symptoms, moreover some have only two to three distinguished symptoms. Those schizophrenia syndromes that have similar symptoms could potentially create errors in the process of determining the type of mental disorder of schizophrenia syndrome. Based on the above problems an expert system application will be made to diagnose the type of mental disorder from schizophrenia syndrome, and due to the unavailability of such applications that can help the doctor at the Jiwa Menur mental hospital. This system uses the fuzzy expert system method. This method will track each of the symptoms experienced by the victim of schizophrenia syndrome, and matching the symptons with existing rules to produces a diagnosis report. The results of diagnostic testing with expert knowledge of the system indicates that the system is able to detect the type of mental disorder on schizophrenia syndromes with 87,5% accuracy of the diagnostic result, which has been implemented to the eight victims. This system also provide treatment based on the types of schizophrenia experienced by the victim. Keyword : expert system, fuzzy expert system, mental disorder, skizofrenia syndrome